Sports confinement and new technologies: coaches perspective - Verzani, Renato Henrique [UNESP]; Morao, Kauan Galva [UNESP]; Bagni, Guilherme [UNESP]; Machado, Afonso Antonio [UNESP]; Souza Serapiao, Adriane Beatriz de [UNESP] (Inst Brasileiro Pesquisa & Ensino Fisiologia Exercicio-ibpefex, 2020)
The formation in football is quite complex, requiring constant reflections on the new realities that emerge, such as the immersion in the environment of virtual social networks and the use of technologies, that add new insights to debates such as the importance of sports confinement, for example. This type of strategy is often adopted at competitive times, mainly aimed at increasing concentration. Thus, the aim was to understand the coaches' view of the importance of the confinement context and the possible changes that new technologies have brought to this reality. Ten coaches were interviewed, with a mean age of 47 years (+/- 11,5). As a result, most coaches find this confinement environment good and important. It is also possible to realize that there is an impact of technologies in this context, and despite considering positive aspects regarding social networks, most think that the use of mobile phones can compromise attention at important times. However, most do not consider it correct to remove them. Therefore, it was possible to verify that there is still an appreciation of the environment of confinement by the coaches, as well as that there is an impact of the new technological demands on it, which can then be an educational opportunity for young people about the related risks and disadvantages. Professionals' reflections on new demands are fundamental, planning effective attitudes and avoiding causing negative situations that can make the situation worse and generate more stress.
Keywords: Sport psychology; Football; Technological development